Radar Cross Section Reduction of a Cavity in the Ground Plane (Communications in Computational Physics, 2020)
This paper investigates the reduction of backscatter radar cross section (RCS)for a rectangular cavity embedded in the ground plane. The bottom of the cavity iscoated by a thin, multilayered radar absorbing material (RAM) with possibly differentpermittivities. The objective is to minimize the backscatter RCS by the incidenceof a plane wave over a single or a set of incident angles. By formulating the scatteringproblem as a Helmholtz equation with artificial boundary condition, the gradientwith respect to the material permittivities is determined efficiently by the adjoint statemethod, which is integrated into a nonlinear optimization scheme. Numerical exampleshows the RCS may be significantly reduced.